2019
DOI: 10.1364/oe.27.035279
|View full text |Cite
|
Sign up to set email alerts
|

Kilopixel array of superconducting nanowire single-photon detectors

Abstract: We present a 1024-element imaging array of superconducting nanowire single photon detectors (SNSPDs) using a 32 × 32 row-column multiplexing architecture. Large arrays are desirable for applications such as imaging, spectroscopy, or particle detection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 26 publications
0
125
0
2
Order By: Relevance
“…The readout in case of an SNSPD array is another key technology for array application because the detectors are operated at considerably low temperatures. Some inspiring results and studies have been recently observed [98,198]. For example, the first kilopixel SNSPDs with row-column multiplexing architecture were demonstrated in 2019 [98].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The readout in case of an SNSPD array is another key technology for array application because the detectors are operated at considerably low temperatures. Some inspiring results and studies have been recently observed [98,198]. For example, the first kilopixel SNSPDs with row-column multiplexing architecture were demonstrated in 2019 [98].…”
Section: Discussionmentioning
confidence: 99%
“…Some inspiring results and studies have been recently observed [98,198]. For example, the first kilopixel SNSPDs with row-column multiplexing architecture were demonstrated in 2019 [98]. However, their performance, such as efficiency and uniformity, should be further improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S UPERCONDUCTING devices are revolutionizing a wide range of research and technological fields including quantum computing [1]- [4], nanowire single-photon detectors [5], X-ray microcalorimeters [6], submillimeter bolometers [7], and Microwave Kinetic Inductance Detectors (MKIDs) [8]- [11]. These applications require increasingly large superconducting arrays, which present the common technical challenge of transporting microwave signals from the cold device stage to room temperature without losing or corrupting the signal or conducting excess heat to the cold stage.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting nanowire single-photon detector device development remains a highly fruitful research area, with academic research groups, national laboratories and start-up companies all engaged. Important avenues of current development include the scale-up from single-pixel devices to large scale arrays [10], integration with complex waveguide circuits [11] and extension of photon counting performance into the ultraviolet and mid-infrared spectral regions.…”
mentioning
confidence: 99%